That Long Silence: Journey from Ignorance to Knowledge: Exploring the Plight and Empowerment of Indian Women in Shashi Deshpande's Works (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Women writers like Shashi Deshpande has left no stone unturned inprobing the tortured psyche of woman to present their hidden desires, aspirant,frustrations, pains and of course dilemma-what to do or not do. There is nodenying in the fact that Shashi Deshpande tried her level best not only tohighlight the plight of traditional Indian woman but also went further to offera positive way. Though there is no dearth of Indian female writers who showtheir concerns for Indian women, but it is quite commendable for those womenwriters who offered a radical yet reasonable way.